Growth and productivity of sesame as a function of mineral and organomineral fertilizer (Research, Society and Development, 2026)
Sesame has been gaining ground among farmers. To increase production, it is necessary to properly feed the crop, which can be achieved through mineral or organomineral fertilizers. The objective of this study was to evaluate the morphological and productive development of sesame in relation to different sources of nutrient supply. An experiment was established with the cultivar BRS Anahí, carried out in randomized blocks, with four treatments and four replicates, two treatments with mineral fertilizer and two treatments with organomineral, with different topdressing fertilization doses, 60 kg N and 120 kg N. Plant height, stem diameter, number of plants per ha, number of capsules per plant, grain weight per plant, weight of 1,000 grains and grain yield were evaluated. Fertilization promotes an increase in the morphological development of the sesame plant, presenting an advantage in height and diameter with the use of organomineral fertilization and urea as topdressing. Mineral fertilization associated with 120 kg of topdressing fertilization showed better yield.